The leptomeninges as a critical organ for normal CNS development and function: First patient and public involved systematic review of arachnoiditis (chronic meningitis) - Carol S. Palackdkharry; Stephanie Wottrich; Erin Dienes; Mohamad Bydon; Michael P. Steinmetz; Vincent C. Traynelis (PLoS ONE, 2022)
Background & importance This patient and public-involved systematic review originally focused on arachnoiditis, a supposedly rare “iatrogenic chronic meningitis” causing permanent neurologic damage and intractable pain. We sought to prove disease existence, causation, symptoms, and inform future directions. After 63 terms for the same pathology were found, the study was renamed Diseases of the Leptomeninges (DLMs). We present results that nullify traditional clinical thinking about DLMs, answer study questions, and create a unified path forward. Methods The prospective PRISMA protocol is published at Arcsology.org. We used four platforms, 10 sources, extraction software, and critical review with ≥2 researchers at each phase. All human sources to 12/6/2020 were eligible for qualitative synthesis utilizing R. Weekly updates since cutoff strengthen conclusions. Results Included were 887/14286 sources containing 12721 DLMs patients. Pathology involves the subarachnoid space (SAS) and pia. DLMs occurred in all countries as a contributor to the top 10 causes of disability-adjusted life years lost, with communicable diseases (CDs) predominating. In the USA, the ratio of CDs to iatrogenic causes is 2.4:1, contradicting arachnoiditis literature. Spinal fusion surgery comprised 54.7% of the iatrogenic category, with rhBMP-2 resulting in 2.4x more DLMs than no use (p<0.0001). Spinal injections and neuraxial anesthesia procedures cause 1.1%, and 0.2% permanent DLMs, respectively. Syringomyelia, hydrocephalus, and arachnoid cysts are complications caused by blocked CSF flow. CNS neuron death occurs due to insufficient arterial supply from compromised vasculature and nerves traversing the SAS. Contrast MRI is currently the diagnostic test of choice. Lack of radiologist recognition is problematic. Discussion & conclusion DLMs are common. The LM clinically functions as an organ with critical CNS-sustaining roles involving the SAS-pia structure, enclosed cells, lymphatics, and biologic pathways. Cases involve all specialties. Causes are numerous, symptoms predictable, and outcomes dependent on time to treatment and extent of residual SAS damage. An international disease classification and possible treatment trials are proposed.